EFFECTS OF ACUPUNCTURE ON RHEUMATOID ARTHRITIS: A SYSTEMATIC REVIEW AND META-ANALYSIS - Li, Jing; Yang, Jie; Wu, Song; Wang, Ming-Rui; Zhu, Ji-Min (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: The aim of this study was to evaluate the efficacy of acupuncture for treating rheumatoid arthritis (RA).Materials and Methods: The literature were searched using 6 databases, including Pubmed, Embase, Chinese BiomedicalLiterature Database, China National Knowledge Infrastructure, VIP and Wanfang database up to December 2013, without languagerestrictions. All randomized clinical trials (RCTs) comparing acupuncture treatment with non-acupuncture treatment of RA wasconsidered. Methodological quality was assessed using the Jadad score.Results: After strict screening, a total of 21 studies containing 1772 participants were included. The meta-analysis indicated that asignificant benefit of acupuncture compared with non-acupuncture on improving the symptoms of RA (pooled RR = 1.19, 95% CI1.08–1.31, Z = 3.47, P = 0.001). In the subgroup analysis, 9 RCTs showed significant effects of acupuncture for response ratecompared with western medicine (RR = 1.26, 95% CI 1.02–1.55, Z = 2.19, P = 0.028); 5 RCTs showed significant effects ofacupuncture plus traditional Chinese drug compared with traditional Chinese drug (RR = 1.17, 95% CI 1.07–1.29, Z = 3.31, P =0.001); 5 RCTs showed beneficial effects of acupuncture plus western medicine compared with western medicine (RR = 1.27, 95%CI 1.06–1.53, Z = 2.56 P = 0.01).Conclusion: This meta-analysis demonstrates that acupuncture may have a favorable effect on treating RA. However, the evidencewas limited by the small sample size and the low methodological quality. Considering the potential of acupuncture, more researchesand well-designed, rigorous and large clinical trials are needed.